Scholar-activist transdisciplinary research praxis for blue justice in South Africa: perspectives from the South African Coastal Justice Network scholar-activist archive - Pereira-Kaplan, Taryn Leigh (Rhodes University, Faculty of Education, Department of Secondary and Post School Education)
This PhD thesis is an applied study on the research praxis of transdisciplinary (TD) scholar-activists contributing to social movements for environmental justice on the coasts and in the oceans ('blue justice'). I wrote this thesis from my position as the coordinator of the Coastal Justice Network (CJN), which is a component of the Global Challenge Research Fund One Ocean Hub's TD ocean governance programme. The CJN is a grouping of South African TD scholar-activists working collaboratively in processes of knowledge co-production with small-scale fishers (SSFs) and other coastal communities. These SSFs are leading resistances to blue injustice from the margins of ocean governance. Within a solidarity and environmental justice orientation to TD ocean research, CJN researchers and SSFs have responded together to a wide range of blue justice issues between 2020 and 2024 and, in doing so, have co-generated an activist archive. This thesis draws on the activist archive to surface core practices and priorities for research that contribute to movements for blue justice. The study was developed as a PhD portfolio through five papers, with an introduction and conclusion. The main aim of this study was to explore dimensions of scholar-activist TD research praxis and associated contributions to advancing blue justice in transformative ocean governance. In doing this, it sought to address some of the gaps in blue justice TD research, most notably the need for a deeper understanding of how to centre the voices and contributions of those most affected by environmental justice concerns. It also addresses the role of scholar-activist researchers practised as a form of political solidarity and reflexive co-engagement. The main research question is: How can scholar-activist transdisciplinary research praxis contribute to advancing blue justice in transformative ocean governance in South Africa? Methodologically, the study uses a form of activist ethnography, which is a scholar-activist methodology that includes an explicit political commitment to engagement and to generating knowledge for activism purposes. Methods within activist ethnographic research include participant and self-observation, critically reflexive "thick" descriptions of context and practice, interviews and conversations, direct political actions with activist partners and facilitation of mutual learning. At the centre of this work is the co-constructed scholar-activist archive, which offers a record of four years of such TD scholar-activist praxis. This thesis and the papers presented as part of the thesis all draw on the co-produced scholar-activist archive constructed out of the social movement work of the SSFs in collaboration with CJN researcher's TD scholar-activist research praxis over four years, representing the type of activist ethnography referred to above. Compiling and organising the archive was one important level of analytical/synthesis work I undertook. I also drew on the archive to make visible key facets of blue justice work and reflected on this, making up three different levels of analytical work with the archive: 1) Constructing and organising the archive, 2) Selection of key foci in the archive, and 3) Meta-reflections. Through this approach, I address the main research question via four sub-questions, each the focus of a paper in this PhD by publication. Why is there a need to advance scholar-activist TD practice in transformative ocean governance research? This question is addressed in Paper 1 (Chapter 2 of this thesis). How can scholar-activists in blue justice support just and inclusive views of ocean governance? This question is addressed in Paper 2 (Chapter 3 of the thesis). What methods in blue justice research enable plural knowledges and perspectives for co-engagement? This question is addressed in Paper 3 (Chapter 4 of the thesis). How is blue justice resistance expressed and acknowledged as a key feature of inclusive ocean governance? This question is addressed in Paper 4 (Chapter 5 of the thesis). What emerges as key lessons for scholar-activist TD researchers in blue justice? This question is addressed in Paper 5 (Chapter 6 of the thesis) and in the meta-reflection in Chapter 7. The thesis as a whole offers: 1. Identification of a core practice, centred on "transformative space making" for care- ful, responsive and reflexive solidarity networks "“ 'net-work' "“ that allows community-based activists and social movements to leverage the kinds of research support they need when they need it. 2. Insight into participatory ocean governance and socially just ocean protection, practised through an 'agonistic' and counter-hegemonic knowledge co-production emergent from this form of TD scholar-activism. 3. Methods and guidance for these practices, with specific emphasis on agonistically plural and inclusive methods of blue resistance. 4. Insights into the positionality and ethical tensions of TD scholar-activist researchers. The study offers an empirical case of how a CJN, through TD scholar-activist praxis, can contribute to blue resistance and blue justice. The reflective chapter (Chapter 7) shows that this type of TD scholar-activist praxis is not without challenges and limitations; through a reflexive review of these, the study offers direction for further research. It also points to the roles of scholar-activists working in solidarity with SSFs in pursuit of blue justice. Overall, the thesis offers an orientation for TD researchers interested in aligning their research praxis with social movements working in counter-hegemonic ways for environmental justice.
Keywords: Student movements -- South Africa; Environmental justice; Ocean governance; Blue justice; Small-scale fisheries -- South Africa; Interdisciplinary research